2009
DOI: 10.1007/s00520-009-0632-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of deep, continuous palliative sedation at home: a retrospective, single-institution study

Abstract: A midazolam-based protocol for PSH is feasible and effective. Our results need to be confirmed by prospective, multicentric, controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 27 publications
5
62
0
Order By: Relevance
“…The principal reason to begin PS was agitated delirium, with dyspnea being the second indication in about 20% of patients. This is in accordance with previous retrospective studies performed at home by our group and other authors, 7,10,11 and in contrast with older data. 12,13 It is likely that a modern approach and greater opioid availability make pain an infrequent indication for PS.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The principal reason to begin PS was agitated delirium, with dyspnea being the second indication in about 20% of patients. This is in accordance with previous retrospective studies performed at home by our group and other authors, 7,10,11 and in contrast with older data. 12,13 It is likely that a modern approach and greater opioid availability make pain an infrequent indication for PS.…”
Section: Discussionsupporting
confidence: 94%
“…Then, a small number of patients who survived more than 24 hours required further dose increments, with an escalation index of about one in the three patients who survived four days, with doses even lower than those reported in other studies. 11 Of interest, the use of midazolam out of hospital, subcutaneously or intravenously, is off-label, although both home care programs have direct contact with hospitals or hospices and drugs are provided by these institutions.…”
Section: Discussionmentioning
confidence: 99%
“…9 The principal symptom to be relieved with PS was delirium; alone or in combination with other symptoms, it was the indication for PS in about 70% of patients. This confirms recent data in the home care setting 3,7,17 and in a pioneer study, 8 and is similar to data reported in a palliative care unit population. 16 Dyspnea was the second most frequent reason to start PS (about 43% of patients).…”
Section: Discussionsupporting
confidence: 92%
“…16 It is likely that hospitalized patients tend to have a greater symptom burden than those who remain at home or patients are admitted to hospital as an emergency because of the development of refractory symptoms close to death. 7,8 Finally, the different environment at home could potentially influence the decision to start PS; factors include lack of a continuous bedside presence, family cooperation, time for planning, and decision making in case of an emergency. 9 The principal symptom to be relieved with PS was delirium; alone or in combination with other symptoms, it was the indication for PS in about 70% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation